Pengaruh Pemberian Kompres Daun Kubis (Brassica Oleracea Var Capitata L.) Terhadap Penurunan Bendungan ASI - Khairatun Nazira; Rita Riyanti K (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Background: Based on the 2015 Indonesia Demographic and Health Survey data, out of 77,231 (37.12%) postpartum mothers, 35,985 (15.60%) experienced breast milk retention. ASI dam is a narrowing of the lactiferous duct, so that the rest of the milk collects in the duct system which causes swelling. One of the efforts to overcome breast milk dams is by non-pharmacological methods, namely using cabbage leaf compresses on nipples that experience pain and swelling or breast milk dams, cabbage leaf compresses are done for 20?30 minutes or until the cabbage wilts, done once a day for 3 days . Objective: To determine the effect of giving cabbage leaf compresses to reducing breast milk dams. Methods: quantitative with the Pre Experiment design and the One Group Pretest Posttest approach with 30 samples. Results: The majority of the breast milk dam scale before being given cabbage leaf compresses is Scale (score ) 4, namely 16 respondents. The majority of breast milk dam scales after being given cabbage leaf compresses are Scale (score ) 1, namely 28 respondents. Conclusion: There is an effect of giving cabbage leaf compresses to the reduction of the ASI dam.